Analisis Butir Soal Asesmen Sumatif Akhir Tahun (ASAT) Mata Pelajaran Ekonomi Kelas X di SMAN Kalisat - Eka Nurcahya; Sukidin Sukidin; Choirul Hudha (Jurnal Evaluasi Pendidikan, 2026)
The study aimed to analyze the quality of ASAT economics test items based on three aspects using a quantitative approach using Anates. A total of 30 multiple-choice questions with 356 student answers were analyzed in this study. Data were collected using document and interview methods. The results showed that 96.7% of the questions were valid, 56.7% were categorized as easy, and the effectiveness of distractors varied with a total of 46% effective distractors, and the overall questions were good based on the omit aspect. This study only provides recommendations for ideal test items based on these three aspects, while the final decision on follow-up on the ASAT questions is left to the economics teacher as the question compiler. The conclusion shows that most questions are suitable to be stored in the ASAT question bank with revisions to less effective distractors to improve the quality of the questions. Keywords item validity, level of difficulty, distractor effectiveness, economics summative assessment